Seroprevalence of leptospirosis in stray dogs from Patos city, state of Paraíba, Brazil - Batista, Carolina de Sousa Américo; Azevedo, Sérgio Santos de; Alves, Clebert José; Vasconcellos, Sílvio Arruda; Morais, Zenaide Maria de; Clementino, Inácio José; Lima, Fabiano de Silva; Araújo Neto, José Othon de (Brazilian Journal of Veterinary Research and Animal Science, 2004)
This work aimed to survey the prevalence of leptospirosis in stray dogs from Patos city, state of Paraíba, Brazil. This study was held during the period of February to April of 2003, when 130 serum samples were collected. The diagnostic method run for leptospirosis was the microscopic agglutination test, using a batch of 22 leptospiral serovars. The most prevalent serovars were found crossing the results of frequency and titer of agglutinins. The results obtained indicated a prevalence of 20% and most frequent reactant serovars were autumnalis (20%), pomona (17,5%), grippotyphosa (10%) e patoc (10%).